2021
DOI: 10.1111/jfpp.15283
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size distribution on nutritional composition, microstructural and antioxidant properties of orange and purple‐fleshed sweet potato flour

Abstract: Influence of particle size distribution on nutritional composition, microstructural, physicochemical, and antioxidant properties of orange and purple‐fleshed sweet potato flour (SPF) with particle sizes 75–355 µm were investigated. As particle size decreased, protein content, water absorption capacity, and water solubility index of both SPF decreased, whereas starch, reducing sugar, and crude fat increased. Total polyphenol contents (TPC) in purple‐fleshed SPF (8.25–9.27 mg GAE/g DW) were higher than orange on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
(64 reference statements)
3
12
1
Order By: Relevance
“…These authors observed that according to the particle size selected for these flours, the starch content could vary up to 20%; thus, in flours of sizes > 32 mesh, 42-80 mesh and 125-400 mesh, the starch content was 50.6%, 60.2% and 68.4%, respectively, indicating that large agglomerates could accumulate in the first two fractions. A similar effect was observed in yam (Ipomoea batatas) flours from Hebei (China), and the starch percentages obtained (43.58%), similar to those of the present work, presented a particle size of 355 µm; however, with particle size 75 µm, these authors obtained a somewhat higher content of starch (61.90%) [44]. The increase in starch with smaller particle sizes is attributed to the breakage of the flour structure so more active sites are exposed for enzymatic degradation [45].…”
Section: Moisturesupporting
confidence: 91%
See 1 more Smart Citation
“…These authors observed that according to the particle size selected for these flours, the starch content could vary up to 20%; thus, in flours of sizes > 32 mesh, 42-80 mesh and 125-400 mesh, the starch content was 50.6%, 60.2% and 68.4%, respectively, indicating that large agglomerates could accumulate in the first two fractions. A similar effect was observed in yam (Ipomoea batatas) flours from Hebei (China), and the starch percentages obtained (43.58%), similar to those of the present work, presented a particle size of 355 µm; however, with particle size 75 µm, these authors obtained a somewhat higher content of starch (61.90%) [44]. The increase in starch with smaller particle sizes is attributed to the breakage of the flour structure so more active sites are exposed for enzymatic degradation [45].…”
Section: Moisturesupporting
confidence: 91%
“…The increase in starch with smaller particle sizes is attributed to the breakage of the flour structure so more active sites are exposed for enzymatic degradation [45]. In parallel, it has also been observed that the sugar content may increase slightly for the finest particle sizes, while decreasing for medium and coarse particle sizes, attributing this fact to the hydrolysis of starch into oligosaccharides and monosaccharides in the flour [44].…”
Section: Moisturementioning
confidence: 96%
“…In addition, there were no significant differences among flours produced at 80 °C with one and two grindings. Azeem et al observed a similar trend: starch content increased as particle size decreased in SPFs …”
Section: Resultsmentioning
confidence: 56%
“…The same behavior was reported by Azeem et al in SPFs. They attributed this behavior to the individual hydration capacity of particles, intercellular microstructure, and degree of arrangement of hydroxyl groups in covalent bonds between chains of starch . Kerr et al reported that the WHC of cowpea flour was significantly less in finely milled flours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation